2012
DOI: 10.1119/1.3703549
|View full text |Cite
|
Sign up to set email alerts
|

Online Prelectures: An Alternative to Textbook Reading Assignments

Abstract: To engage students in a more meaningful discussion of course material and prompt their higher thinking skills, most instructors expect students to read the course textbook for initial exposure to the course content before class. However, as many instructors are aware, most students do not read their textbook throughout the quarter.1,2 At California State Polytechnic University, Pomona (Cal Poly Pomona) we have adopted web-based multimedia learning modules (MLMs) as prelecture assignments to help students to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
2
26
0
5
Order By: Relevance
“…For example, improved student learning and attitudes towards instruction have been found when reading assignments have been replaced with on-line multimedia videos in physics classes across various institutions [5][6][7]. In particular, it has been shown that students arrive to class better prepared for learning when completing MLMs versus traditional reading assignments for large-enrollment lecture-based courses and hybrid on-line formats [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, improved student learning and attitudes towards instruction have been found when reading assignments have been replaced with on-line multimedia videos in physics classes across various institutions [5][6][7]. In particular, it has been shown that students arrive to class better prepared for learning when completing MLMs versus traditional reading assignments for large-enrollment lecture-based courses and hybrid on-line formats [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A more in-depth discussion of how the authors of the MLMs utilized the relevant literature in the design process is available in reference [8]. Furthermore, the efficacy of the MLMs has been verified in multiple other settings [5][6][7][8][9].…”
Section: Multimedia Learning Modulesmentioning
confidence: 99%
“…Benefits such as increased student engagement, increased feedback between teacher-students and among students, as well as the degree of student independence have been documented in several literatures (Goodwin & Miller, 2013;Roehl, Reddy, & Shannon, 2013;Sadhaghiani, 2012). Although the benefits have been widely studied, not many have applied to teacher training programs since most of the application of flipped classrooms is done in the field of science (Sadaghiani, 2012). Meanwhile, providing innovative and creative learning models should be the foundation of teacher training programs, because optimal learning is done by having a hands-on experience.…”
Section: Theorymentioning
confidence: 99%
“…Though their sample size was small (45 students), they found that students who watched the multimedia presentations scored nearly one standard deviation higher than students who read the textbook [7]. Moreover, there is evidence that students are more likely to watch videos than read the textbook before class [8].…”
Section: Finding Videos and Other Resourcesmentioning
confidence: 99%